Lower respiratory tract infections associated with rhinovirus during infancy and increased risk of wheezing during childhood. A cohort study. - Cristina O'Callaghan-Gordo (Public Library of Science (PLoS), 2013)
Background and objectives Although association between respiratory syncytial virus infection and later asthma development has been established, little is known about the role of other respiratory viruses. Rhinovirus was considered a mild pathogen of the upper respiratory tract but current evidence suggests that rhinovirus is highly prevalent among children with lower respiratory tract infections (LRTI). The aim of the study was to evaluate whether LRTI hospitalization associated with rhinovirus during infancy was associated with an increased risk of wheezing - a proxy measure of asthma - during childhood. Methods During a 12 months period, all infants <1 year admitted to Manhiça District Hospital with symptoms of LRTI who survived the LRTI episode, were enrolled in the study cohort. Nasopharyngeal aspirates were collected on admission for viral determination and study infants were classified according to presence or not of rhinovirus. The study cohort was passively followed-up at the Manhiça District Hospital for up to 4 years and 9 months to evaluate the association between LRTI associated with rhinovirus in infancy and wheezing during childhood. Findings and conclusions A total of 220 infants entered the cohort; 25% of them had rhinovirus detected during the LRTI episode as opposed to 75% who tested negative for rhinovirus. After adjusting for sex and age and HIV infection at recruitment, infants hospitalized with LRTI associated with rhinovirus had higher incidence of subsequent visits with wheezing within the year following hospitalization [Rate ratio=1.68, (95% confidence interval=1.02-2.75); Wald test p-value = 0.039]. No evidence of increased incidence rate of visits with wheezing was observed for the remaining follow-up period. Our data suggest a short term increased risk of wheezing after an initial episode of LRTI with RV.